UJI INFEKSI Cylindrocladium sp. PADA KLON HIBRID Eucalyptus grandis x Eucalyptus urophylla (INFECTION TEST Cylindrocladium sp. ON HYBRID CLONES OF Eucalyptus grandis x Eucalyptus urophylla) - Junita Herawati Hutasuhut; Nelly Anna; Edy Batara Mulya Siregar (Peronema Forestry Science Journal, 2015)
Eucalyptus leaf sp. is a fast-growing plant species as raw material pulp industry at large.  At the time of this plant breeding susceptible to deases. One is a deseases caused by a fungal leaf Cylindrocladium sp. The objectives of this research aims to characterize the symptoms of foliar diseases and measure the intensity and widespread attacks caused by Cylindrocladium sp. the clone IND 47, IND 61 and IND 66. Infection done bye spraying inoculants fungi in this experiment used three clone of plant E. grandis x E. urophylla age of two month from the observation of the symptoms of the diseases symptoms appear, calculated intensity and widespread attacks. The results showed symptoms on leaves caused by infection Cylindrocladium sp. the three clones have the same symptoms are red spots on the leaf surface and then develop into red-brown spots. In measuring the intensity of the attacks and extensive third attack resisten clones are clones Keywords: Cylindrocladium sp., Hybrid Clones of Eucalyptus, Infection Test